Serbest piyasa ekonomisine geçiş sürecinde Bulgaristan örneği - Uğur, Barış (My University, 2001)
A great changement was occurring after fell down the Berlin Wall in East Europe, in 1989. The countries had begun to new period with high debts and inflation by these changements. East European countries have a common feature by carry out the transition period politics by rapidly in this process. So, it was necessity on stabilization politics but not easy. At result, privatization and restructure got an importance. I – THEORICAL AND CONSEPTIONAL FRAME OF MARKET ECONOMY Free market economy has the same philosophy and idea with liberalism. Economical liberalism is defended the free competition, reducing the customs taxes, import freedom and resisted to interference of state on the economy. Classical economy’s base is economical freedom and market economy. Market economy is relying on free competition and private enterprise. Price mechanism and world prices are important. Interference of state must be in minimum levels. Public sector must be reduced. Basic factors such as wage, capital and foreign currency must reflect the real market prices, must get an importance to external trade. 1-DEVELOPMENT OF MARKET ECONOMY 1.1. CLASSIC REVIEW Free trade, specialization only on one field, annihilate the obstacles such as customs and quotas, interferences of state on the market are most important according to Adam Smith, which lived in 18th century. A specialization between nations must be obtained according to Ricardo. So, it must be an exchange on the entire world. 1.2. NEO-CLASSIC REVIEW Alfred Marshall, Leon Walras and Carl Menger is an echol. The state must be more active to improve the poor part of community and must create the opportunities on the market, get the taxes from revenues and wealth, finance the education, health, park and city planning, defence the personal freedom, private property and open markets, manufacture the public commodities. 1.3. ORDO-LIBERALISM REVIEW It is different from classic liberalism. Economical regularity is social which emerges in an evident process, not natural. Social and juridical standards emerge the economical system. Price, monetarily stability, sciences, stability and durability on economical politics are important to emerging of market economy. Basic aim is bring to existence an economical constitution. 2- BASIC ELEMENTS OF MARKET ECONOMY Basic factors are enterprising, competition, economical ideas and attitudes. Enterprising is a person which makes unity the manufacturing factors, makes direct the investments, begins to motion by utilize the signals from internal and external markets, gets the share on productivity and determines the firm profit. Basic aim is profit. Competition is social event, protects the personal, which works with high productivity against to personal, which works with low productivity, uses the sources most effectively. Buyer and seller number must be too much in this system. Competition is opposed to monopolization but necessity laws and politics have to support it. ECONOMICAL IDEAS AND ATTITUDES It includes price, wage, interest, hire and foreign currency. Price system occurs freely according to rate of request and demand conditions. At this straight, firms and consumers must carry out their decisions freely. 3- MARKET MECHANISM FLOW AND ROLE OF SOURCE DISTRIBUTION Consumers and producers have activities on the market economy. The prices are determined according to the lowest cost and to the highest profit. Ideal special future is high productivity, low profit and high production. Competition reduces the profit to the lowest level. Main mechanism on free market is price. If the relative scarcity is enough, request and demand is more or less equal. Producers and consumers may have a decision according to the price indicator and request and demand. This case makes lead the manufacturing, increases the alternatives, also economical activities make an harmony against to conditions. The evident features of market economy are free decision, liberty on preferences, a great price mechanism and competition. So, economical stability is obtainable. Interferences may apply on the market economy for public health, regulations on economical activities, protect the consumers. These motions are generally precautions to control of drugs and drink manufacturing and consumption, annihilation of harmful on public health, growth the power on economic morals, make grow the quality, regulation on manufacturing and marketing. The state may meddle with economy to development rapidly. For example, the state may encourage the saving, increase the rates of interest, decrease the taxes to get on the saving, provide the precautions on investment. The buyers and sellers cannot determine the price on one’s own on free competition market. Otherwise monopoly, trust and cartels may occur, stability may out of order between commodity and services. Market economy may deviate from the rules on two main categories. Manufacturer, buyer and seller may make deviate from the rules. Especially trade unionization is effective on this deviation.The state may interfere in economy by taxes, if social and individual advantages different, it may deviate from competition market. The state is exist in every kind of economy and serves to people with harmony and politics and social philosophies of our age. Also it provides security, education and health services but it doesn’t determine the prices. It is one of the biggest manufacturers at the same time. II – HISTORICAL WIEW TO BULGARIAN ECONOMY IN THE TRANSITION PERIOD OF FREE MARKET ECONOMY 1. BASIC SOCIAL AND ECONOMICAL INDICATORS 1.1. GENERAL The form of government is republic, capital is Sofia, Population is 8.297.000(1997), increasing of population is %0. 7, distinctive characteristics in common with Turkishs, Pomaks, Russians, Gipsies, Tatars, Jewishes are in 16 percent. Estimated agricultural area is 1/ 3 and woodland is 1/ 3 of all the land. Charcoal, petroleum, natural gas, ferrum and sources except metal are too much. Bulgaria can’t use the money too much on surroundings cause of economical lacks. Too many people are migrated to Turkey reason of economical lacks after communism regime. Population is decreased year by year, but unemployment. 2. BULGARIA BEFORE 1989 Ottoman empire had governorship on the Bulgaria more 500 years till 1908. Then, Bulgarian Kingdom is founded in 1908. Stamboliyski is in powered from Farmer Party in 1920. A new fascism supporter government is founded but communists and farmers were outside of government. Bulgaria is allied with Germany in 1941. Although a new government was found in 1944, the republican regime with referendum is founded in 1946. The new constution is validated in 1947. Cercenkov is in powered in 1950, relations with U.S.A. were out of order and membership of United Nations was validity in 1955. The new constitution is validated in 1971. T.Jivkow is in powered continually, became arrested cause of irregularity in 1990 and then, again a new constitution is validated. Communist Party is made to take out of only one party. In that year, state’s name is changed to Republic of Bulgaria and removed the communist symbols from flag. Privatizational laws are validated with Jelev in 1992. The Government of Videnov is contraried the privatization in 1994. Peter Stoyanov is Nato’s supporter and he was president in 1996. United Democratic Forces is in powered with 52 percent of vote after selections in 1997. 2.1. COMECON AND COLLAPSING OF SYSTEM Comecon is a union that emerged by East European Countries. Bulgarian economy has begun to transition period with some negative ness like other East European countries causes of political incompetence and dissociating end of 1980s. Bulgaria which had more than 60 percent of export to associate but it had couldn’t find the new markets cause of inadequate ship of quality standards and had an old technology. Foreign currency reserves are high level. It has too many debts, political incompetent ship in the land. Financial system is not conformity to market economy and also could not claim 2 million dollars of money owing from Iraq because of golf war. So, Bulgaria couldn’t save from crisis because of above reasons. 2.2 GENERAL ECONOMICAL DEVELOPMENT AND SECTORS Bulgarian manufacturing industry basically is founded on textile, wooden engrave, leather products and food prep rationing sectors. Bulgaria had realisation the attacks on the heavy industry that supported by S.S.C.B. after 2nd world war. Production of electro-mechanic and electronic goods in manufacturing sector is reached to an important share since 1970s. The biggest natural wealth of Bulgaria is productive earths. There are not important minerals in Bulgaria. In the following period of 2nd world war, metallurgy and chemical production had an importance. Industry sector had old technology. Its competition is losted the power with disunited of the Comecon. Productivity rates on industry are grown with economical reforms that started in 1979. Economical growing is dynamically continued in spite of reducing the productivity on agriculture sector, building sector and investments in Bulgaria. Especially, price volatility on agriculture sector is a reason of suspicion about real value of growth in 1988 according to 1987. Productions on agriculture and industry of Bulgaria are reduced according to statistics. Main problem on agriculture sector is delivery prices of goods. A stagnation indicator on Bulgarian economy is weakness of building and construction sector. Manufacturing products such as cement and weawing is in necessity. Manufacturing level is inadequate on that area and also unqualificationed organisations have been affected. 2.3 - FOREIGN TRADE There are no definite results on foreign trade reason of inadequate of numerical data’s. However, export is increased up to the rate of 4 percent in 1988 and import is reduced to the rate of 1.8 percent. Bulgaria finance deficit is 600 million dollars result of trade with west countries in 1998. Tourism revenues are positive. Trade connections with Turkey are weak according to another East European countries. 2.4 – PERESTROICA POLITICS The new age on economy with state council’s decision is started in January 9,1989. Activities to get the indepences of firms are velocitied. At the same time, this decision is more benefit to foreign investors too. 3. 1989 – 1997 TRANSITION PERIOD 3.1 – ECONOMICAL REFORM ACTIVITIES Alteration is started in east block countries after 1989 and together with this alteration. Comecon is losted the activity. So, idle capacities are commenced and Bulgaria is losted the production markets. The reforms are making started by new government in February 1991. External trade regime is liberalisation in one direction; this is one of the import nest factors of the reforms. With a decision is accepted in 1989, basic of economical reforms are occurred. Firms had equal rights to execution of economical activities. The laws related to foreign investment are validated in 1992. Commercial banks have gone to consolidation. Prices had freed except 11 basic consumption. Economical activities, government status on economy, foreign trade and foreign exchange regime, price regulations, privatization, tax systems are reorganized about foreign investors. 3.2. SECTORAL CONSTITUTION Industrial sector had the over 50 percent of share on economy until 1990s. 11 private sector’s share with service and trade sector approached to 60 percent between 1992 and 1997. SECTORS Productivity with old technologies on industrial sector is at low level. Engineering sector is developed. Products of textile sector are manufactured at high quality. CHEMICALS Chemical products that have an important mark on export of Bulgaria. They were 1,096 milliard dollars with 22,3 percent in 1997 and 983 million dollars with 19.4 percent of total export in 1998. AGRICULTURE, FOOD AND TOBACCO Rate of plan tablelands are 34 percent in Bulgaria. Totally 304 firms are active on food, drink and tobacco sector. METALLURGY AND MINERSHIP Iron product is 6.2 percent and other than iron is 6.8 percent on all of industry in 1998. In 1997, metallurgy sector is grown up to 117.2 percent with 529 million dollars in total amount of export in Bulgaria. MACHINE Share of machine sector is 13.8 percent in all of industry. Principal are; Machine parts, tractor, bus, ship, building and auto spare parts. CONSTRUCTION Private firms in the sector have share with 13 percent in 1991. That share is grown to 62 percent in 1995 but then; it is reduced reason of financial inadequate ships. TOURISM Tourism revenues are approximately 280 million dollars in 1995. 4.5 million of transits and totally 8 million tourists are visited the Bulgaria in 1996. 3.3. TRADE AFTER ECONOMICAL REFORMS Export of Bulgaria is totally 4.9 milliard dollars in 1997. The import nest export products are fuel oil, other fuels, cooper and its products and nuclear reactors. Import is 4.5 milliard dollars in 1997 and included the product such as mineral fuels, nuclear reactor heaters and spare parts, electric machines, mineral substances, cotton, synthetic fibres, cereals, auto and tractors. 3.4. EXTERNAL DEBTS Rate of the external debts to export revenues were 249.9 Percent in 1993 but then, back to 188.2 percent in 1994. Official external debts were 10.363 dollars in the end of 1997. 3.5. FOREIGN INVESTORS EXTERNAL CAPITAL Most investments with 636.2 million dollars by foreigners are made in 1997. This amount is 526 million dollars in 1998. Principal foreign investors are European countries and U.S.A. A new foreigner investment law is prepared in Oct 1997. Main sectors to investment are industry, trade, finance and tourism. 3.6. COMMERCIAL BANKING State banks are privatization by associate. Regulations relate to control of banking are valitidied by government. In the middle of 1997, a new law on banking are validated after economical crisis in 1996, Central Bank Law are rebuilt. High levels of capital and capital qualifications are obligationed. 3.7. PRIVATIZATION Privatization is started with foundation transformation and privatization belongs to state and municipalities in April 1992. Privatization Agency is built-up. Privatization is realization with totally 836 million dollars between Jan 1, 1993 and Dec 30,1998. Its part of 421.4 million dollars is in 1997 and part of 116 million dollars is realization in 1998. Foundations like ports, telecommunication and, etc.are out of privatization by laws. 95 percent of state firms transformed to form of private limited or nationalization. Share of these firms are belong to state. III. BULGARIA IN EUROPAN UNION AND CONNECTIONS WITH TURKEY 1. BULGARIAN ECONOMY AND CONNECTIONS WITH TURKEY Test and certification operations, metal products except iron, chemical products, cereals, operational petroleum. Products are important substances from Bulgaria to Turkey. Although weaving products, food, chemical products, leather and stout leather products, glass, ceramics, brick products are ones of important from Turkey to Bulgaria. 1.1. CONTENTS OF FREE TRADE AGREEMENT BETWEEN TURKEY AND BULGARIA All taxes and restrictictions on industrial products by signed on European Agreement between European Union and Bulgaria in Mar 8,1993 and validated in Dec 31,1993 will be removed till 2002. Turkey and Bulgaria made easy to particularization into agricultural products market by reduced the taxes for between their selves. End of signed acts, 131 products of 446 that stated to Turkey and 1141 goods of existing on European Union Agreement are liberalization by remove from list of sensitive products. Foreign companies had a partnership rights with corporations and individuals and also foreign individuals had a right on economical activities by law of keeping foreign investors, which is validated in 1992. Same economical rights are recognized between foreigners and Bulgarians and also getting unlimited share from exist companies and companies that will be found. 2. CONNECTIONS WITH EUROPEAN UNION AND FINANCIAL PORTREIT OF BULGARIA 2.1. CONNECTION WITH EUROPEAN UNION OF BULGARIA In the autumn 1989, Berlin wall is demolished and this motion make united the European that had divided to east and west after 2nd world war. Comecon’s mean is continuing the economical dependent ship to Soviet Union. But, most east and west European countries reject it. After these European Union augmented economical and political supports to that countries reason of carry out and conclude the reform, which is started in middle and east European countries. Firstly, a group includes the Turkey is formed by 24 of OECD countries. G24s are transferred to entrust with coordination of support to the European Union Commission. That commission is functionizationed the Phare program that helps on financial and technical areas to Poland and Hungary. Bulgaria, Czechoslovakia, Yugoslavia and Romania in Sept.1990, Albanian, Estonia, Leetonia and Livonia in Jan.1992 and Slovenia in Aug.1992 are included by Phare program. Military regulations on security of West European losted the importance but they are already securely areas. Main political aims that related to Middle and East European countries of European Unions are explained below; a- Encouragement of liberal democratic system with respectful of law’s superiority. b- to be sense on surroundings c- to prevent the ethnical collides d- to prevent the migration to foreign countries at the west. e- Phare program and encouragement of free market economy from planned economy. 2.2. WHAT IS THE PHARE PROGRAM? Phare program’s aim is build the encourage mental conditions to the market economy and to take pains about investments on economies of Middle and East Europe countries. This program includes unfinancable fields by traditional external supports. That supports on the program is formed by credits and encouragements and used for pilot projects related to reorganization of associations. Bulgaria is taken a support of 10.6 millions ECU by include of Phare program. European Union don’t use only Phare program as a tool on politics related to Middle and East Europe countries, except it Includes the programs within own constitution such as ERASMUS and COMETT. 2.3. FIRST PERIOD (before 1989) In this period; trading is developed between Middle and East European countries that named as COMECON COUNTRIES but couldn’t show the same developments against to West Europe in European Union. Soviet Union takes the priority on exporting with countries. Bulgaria is the develop pest country on trade with Soviet Union. 2.4 TRANSITION PERIOD (1989-1992) The great changements occurred on trade in Soviet Union and Middle and East Europe countries from starting the reforms in 1989 to 1992. From 1989,trade and partnership agreements signed with Hungary and Poland then, with Czechoslovakia in 1990,also Bulgaria and Romania in 1991. At the same time, rejection is started on amount of restrictions. Exporting is increased between Middle and East European countries, Soviet Union and European Union other than below too; Devaluation in the countries other than Hungary, - Workings to join into the West European markets reason of re-emerging the losted ones in East European - Import is on peak-level from those countries to Germany after unitized the East and West Europe. 2.5. EUROPEAN AGREEMENTS European agreements are acted end of 1991. Bulgaria-Europe agreement’s date of signature: Mar8, 1993 Date of being inforce: Dec 31,1995 Temporarily agreement: Dec 31,1992 European agreement has been in force in Bulgaria, end of 1995. European agreements are partnership agreements that signed by based on 238th paragraph of Roma agreement and Maastricht agreement. According to that state, increasing of export is an prestipulation to growth the economy with stability. 3. SUCCEED OF STABILITY PROGRAM IN BULGARIA Bulgaria signed on an agreement with IMF to pass over the economical hardships and started the reforms in 1991.Economy is grown at the rates of 2.1 percent in 1995. In 1997,economy has the new crisis related to Yugoslavia crisis and so, Bulgaria signed on a new agreement with IMF.Leva is fixed with 20 DM and 1000 Bulgarian Leva to 1 DM and constructral reforms is started to gain the speed. Economy in Bulgaria grown to positive from 1994 but to the 10.9 percent in 1996. - Inflation rates (%) in Republic of Bulgaria; 1992 1993 1994 1995 1996 1997 1998 82,2 72,8 96,2 62 123,1 1082,3 22,3 After the stand-by agreement with IMF, inflation approached to 22.3 percent in 1998. Annual average of inflation is expected as 7.3 percent in 1999 and 9.0 percent in 2000. Bulgaria is the poorest country according to other east European countries candidate to membership of EU. Bulgarian Leva is determined by rejected the 3 zeros from Detsch Mark. So, new Leva is make related on euro at the rates of 1.95583:euro 1 (Lvl:DMI ). CONCLUSION: Bulgaria is declared the moratorium reason of hardness’s to find an external debt, to refund the capital and interests of external debt. While external debt is 10.6-milliard dollars end of 1990,it has been 12.2 milliard dollars, end of 1993. So, started to paces towards to market economy in Feb 1991. Annual inflation is reduced from 338.5 percent in 1991 to 79.4 percent in 1992. The debts of managements of state are ruined the budget and also a reason to broken balance on economy too. The crisis on foreign currency is occurred in Mar 1994. Reforms have been out of control at the result of that crisis.Leva is devaluated as 100 percent and inflation is reduced to 90 percent on annual average. At this parallel, financial and revenue politics, money and its value are controlled. The debts to foreign countries are decreased to 9.8 milliard dollars with precautions in 1994 and end of 1996. Financial balance are obtained again in the first months of 1995, reduced the inflation and also rate of interests to 72 percent. Rate of exchange (Leva/ $) was 503 percent between Jan 1 and Feb 12,1997. Especially, that increasing was 20-percent/ each day in Feb 1997. Rate of interest was 300 percent in Sep.1996. 14 Banks are bankrupted in that period. Bulgaria had been 1st of the world from inflation increasing speed of view. Inflation, devaluation, unemployment and also wages are on the lowest level in transition period in Bulgaria. Incoming per person is decreased 50 percent between 1989 and 1995. Annual criminal events are increased 3 times more after 1990. Money committee had formed by advice of IMF in Jul 1997. 1Deutsche Mark is indexed on 1 Leva. Qualified personnel with educationed on technical areas is a great potential force of Bulgarian economy. Bulgaria will be completed the transition period when it became to membership of European Union.
Keywords: Bankacılık; Ekonomi; Ekonomik durum ve koşullar